Topography-Driven Surface Renewal - Cerda-Villablanca, E (Nature Publishing Group, 2018)
Natural surfaces excel in self-renewal and preventing bio-fouling, while synthetic materials placed in contact with complex fluids quickly foul 1,2 . We present a novel biophysics-inspired mechanism 3,4 for surface renewal using actuating surface topography, generated by wrinkling. We calculate a critical surface curvature, given by an intrinsic characteristic length scale of the fouling layer that accounts for its effective flexural or bending stiffness and adhesion energy, beyond which surface renewal occurs. The effective bending stiffness includes the elasticity and thickness of the fouling patch, but also the boundary layer depth of the imposed wrinkled topography. The analytical scaling laws are validated using finite-element simulations and physical experiments. Our data span over five orders of magnitude in critical curvatures and are well normalized by the analytically calculated scaling. Moreover, our numerics suggests an energy-release mechanism whereby stored elastic energy in the fouling layer drives surface renewal. The strategy is broadly applicable to any surface with tunable topography and fouling layers with elastic response. © 2018, The Author(s).